Involvement of Metalloproteases in the Fertilization of the Ascidian Halocynthia roretzi - Hitoshi Sawada; Ikuya Hattori; Noritaka Hashii; Takako Saito (Biomolecules)
We previously reported that five astacin-like metalloproteases with thrombospondin type-1 repeats (Tasts) located on the sperm surface are a promising candidate as the protease involved in sperm penetration of the vitelline coat (VC) during fertilization of the ascidian Ciona intestinalis type A (Phlebobranchia). However, whether such a protease is involved in the fertilization of other ascidians is unknown. Here, we investigated the effects of four metalloprotease inhibitors on the fertilization of the ascidian Halocynthia roretzi (Stolidobranchia). Three metalloprotease inhibitors, GM6001, TAPI-0, and TAPI-1, strongly inhibited fertilization at 33 and 11 μM, whereas TAPI-2 weakly inhibited fertilization at 33 μM. In contrast, GM6001NC (negative control) had no effect on fertilization at 100 μM. Furthermore, GM6001 had no inhibitory effect on the fertilization of VC-deprived eggs. The metalloprotease appears to function at the middle or late stage of fertilization. Ten Tast genes were identified in the H. roretzi genome database, among which four genes (HrTast1, HrTast2b, HrTast2c, and HrTast3c) possessed a single transmembrane domain in the N-terminal region. These four genes are transcribed in the testis and ovary, as revealed by RT-PCR. Anti-HrTast2c IgG raised against a peptide corresponding to the Zn-binding consensus sequence weakly inhibited fertilization at 0.5 mg/mL. These results led us to propose that sperm astacin-like metalloproteases may be involved in sperm penetration of the VC during H. roretzi fertilization.